2017
DOI: 10.1242/jcs.207860
|View full text |Cite
|
Sign up to set email alerts
|

PDGF controls contact inhibition of locomotion by regulating N-cadherin during neural crest migration

Abstract: A fundamental property of neural crest (NC) migration is contact inhibition of locomotion (CIL), a process by which cells change their direction of migration upon cell contact. CIL has been proven to be essential for NC migration in amphibians and zebrafish by controlling cell polarity in a cell contact-dependent manner. Cell contact during CIL requires the participation of the cell adhesion molecule N-cadherin, which starts to be expressed by NC cells as a consequence of the switch between E-and N-cadherins d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Our finding that Girdin is involved in actin remodeling at the cell‐cell interface in A431 cancer cell groups (Figure C) supports the model, but it is unknown at present whether it was a direct or indirect effect of Girdin depletion. Another intriguing mechanism for collective migration is that cells maintain CIL to avoid interfering with their neighbors . We previously showed that the Girdin CT domain also binds the cell polarity regulator partitioning‐defective gene 3, which is known to be critical for collective migration and CIL by downregulating actomyosin contractility at cell‐cell contact (Figure E) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our finding that Girdin is involved in actin remodeling at the cell‐cell interface in A431 cancer cell groups (Figure C) supports the model, but it is unknown at present whether it was a direct or indirect effect of Girdin depletion. Another intriguing mechanism for collective migration is that cells maintain CIL to avoid interfering with their neighbors . We previously showed that the Girdin CT domain also binds the cell polarity regulator partitioning‐defective gene 3, which is known to be critical for collective migration and CIL by downregulating actomyosin contractility at cell‐cell contact (Figure E) .…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have begun to reveal the mechanisms of collective invasion of cancer by using in vitro culture models as well as studies of collective migration of cells during embryonic development . These include the contact inhibition of locomotion (CIL) that keeps the integrity of cell‐cell contact and spatially regulated trafficking of cell adhesion proteins such as N‐cadherin . We previously reported that the collective movement of cancer cell groups requires the expression of integrin β1 by the leading cells but not the following cells .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of E-cadherins during embryonic development happens quite early where they play a role in adhesion and compaction of the blastomeres. It also signals the controlled epithelial-to-mesenchymal conversion and regulates developmental processes like cell migration and proliferation [ [31] , [32] , [33] , [34] ]. The migration of mesodermal cell is favoured by downregulation of the E-cadherin and loss of cell adhesion [ [35] , [36] ].…”
Section: Discussionmentioning
confidence: 99%
“…At cell–cell contacts, N‐cadherin signaling function inhibits Rac1 activity and thus inhibits protrusions while promoting Rac1 activation and protrusions at the cellular free edge (Theveneau et al, ). Recently, it was shown that N‐cadherin expression is dependent on PDGFRα/PDGF‐A signaling (Bahm et al, ). The PDGFRα receptor tyrosine kinase and its ligand PDGFA are co‐expressed in CNCCs, and their inhibition prevents N‐cadherin expression, thus resulting in a loss of CIL and inhibiting NCC migration (Bahm et al, ).…”
Section: Ncc Migrationmentioning
confidence: 99%
“…Recently, it was shown that N‐cadherin expression is dependent on PDGFRα/PDGF‐A signaling (Bahm et al, ). The PDGFRα receptor tyrosine kinase and its ligand PDGFA are co‐expressed in CNCCs, and their inhibition prevents N‐cadherin expression, thus resulting in a loss of CIL and inhibiting NCC migration (Bahm et al, ). This pathway therefore achieves cell‐autonomous regulation of CIL by upregulating N‐cadherin during EMT.…”
Section: Ncc Migrationmentioning
confidence: 99%